RECOGNITION OF INDIGENOUS LAND RIGHTS WITHIN THE ENVIRONMENTAL SOCIAL GOVERNANCE (ESG) FRAMEWORK: A LEGAL COMPARATIVE ANALYSIS OF INDONESIA AND THAILAND - Muh. Zulkifli Muhdar; Sri Amlinawaty A. Muin; Salmawati Salmawati; Ruetaitip Tungkasamitra Chansrakaeo (Universitas Lampung, 2026)
This study offers a comparative analysis of the recognition and protection of indigenous land and natural resource rights within the Environmental, Social, and Governance (ESG) framework in Indonesia and Thailand. Using a normative legal method with statutory and comparative approaches, it examines how national legal and institutional systems integrate indigenous rights and how ESG functions as a mechanism for mitigating agrarian and environmental conflicts. The findings show that Indonesia has a stronger legal basis for recognizing indigenous rights through the 1945 Constitution and Constitutional Court Decision No. 35/PUU-X/2012, but faces inconsistent implementation of the Free, Prior, and Informed Consent (FPIC) principle, while Thailand demonstrates more advanced ESG reporting and transparency yet lacks explicit legal protection for indigenous communities. This study positions ESG as a system of social risk governance and underscores the need for stronger synergy among national law, financial institutions, and indigenous participation to achieve inclusive and equitable ESG implementation in Southeast Asia.